The Influence of Brand Authenticity on Brand Loyalty Towards Local Skincare Products: Mediating Role of Brand Attachment - Norris, Teresa; Sari, Diana (Manunggal Halim Jaya, 2026)
This study aims to investigate the influence of consumer perceptions regarding the authenticity of somethinc as a local skincare brand on their level of loyalty, while also comparing the results when mediated by the role of brand attachment. Empirical data were collected from 255 respondents in Indonesia who had purchased Somethinc skin care products at least 3 times for their personal use. The respondent data was processed using Partial Least Squares Path Modeling (PLS-SEM) analysis integrated through Smart PLS 3 software. It was found that brand authenticity doesn't influence brand loyalty directly in the beauty industry. However, brand authenticity can influence brand attachment significantly. Likewise, brand attachment has a significant effect on brand loyalty. Then, the relationship between brand authenticity and brand loyalty becomes significant when mediated by the brand attachment variable. This study contributes to becoming a benchmark for local beauty brands in developing their strategies to gain consumer loyalty.